Pengaruh Orientasi Sudut Anyaman Serat Terhadap Kekuatan Tarik Komposit Poliester Diperkuat Serat Basal - Arsyi Alfatin, Muhamad; Suardana, Ngakan Putu Gede; Agus Suryawan, I Gede Putu (Teknik Desain Mekanika; Vol 10 No 2 (2021): April 2021 : Teknik Desain Mekanika, 2021)
Abstractt Many researchers have been done to create composites with materials of natural origin, so as not to have a negative impact on the environment. For example, basalt fiber is environmentally friendly, which makes its use very attractive. In terms of angular orientation, if you use two directions, it will be longitudinally strong in that direction, but a different strength will be generated if it is pulled in another direction which tends to be weaker. in other words, it is not transversely strong. Therefore, the researchers varied the basalt webbing to make basalt fiber reinforced composites with a woven angle orientation of 0°, 10°, 20°, 30°, 40°, 50°, 60°, 70°, 80°, 90°; and the specimens were cut at an angle of 0°, 10°, 30°, 45°, 50°, 60°. Then the composite testing was carried out with a tensile test. This test needs to be done to determine the tensile strength of the specimens that have been made. This study aims to determine the properties of the tensile strength of the specimens that have been made and the fiber fracture structure. The results of the test show that the specimen with a cut angle of 0° has a very high tensile strength when compared to other specimens that have been made. The tensile strength reaches 180,922MPa, with a length increase of 4.055%, and the modulus of elasticity is 4.552GPa. While the weakest strength was experienced by specimens with a cutting angle of 45° with a tensile strength of 126.531MPa, an increase in length of 3.417%, and a modulus of elasticity of 3.89GPa. Keywords: Direction of fiber, Composite, Basalt Fiber, Impact Test